Efficacy and safety of a restrictive blood transfusion protocol in gynecologic surgical patients - Rachel P. Mojdehbakhsh; Rana Al-Rubaye; Dandi S. Huang; Joseph Connor; Ahmed Al-Niaimi (Elsevier, 2022)
Objectives: This study sought to compare differences in blood transfusion and surgical complication rates before and after the implementation of a restrictive blood transfusion protocol. Methods: On July 1, 2018, our institution implemented a restrictive blood transfusion protocol utilizing a hemoglobin trigger of less than 7 g/dL. Retrospective chart review was completed to review patients undergoing major abdominal surgery by the gynecology and gynecologic oncology services 18 months before, and after initiation of the transfusion protocol. Outcomes included number of patients, units transfused and postoperative complication rates. Complications included reoperation on the day of admission, surgical site infections, wound disruptions, pulmonary, renal, central nervous system, and cardiovascular complications, as well as deep venous thromboses, readmissions, and 30-day mortality. Results: There were 290 people in the pre- and 449 patients in the post-protocol group. A similar number of patients received blood transfusions in both groups (9.3% versus 10.6% p = 0.57). However, significantly fewer units of blood were given post-protocol initiation. For every patient who received a transfusion pre-protocol, 2.66 units were administered compared to 1.2 units after the protocol was initiated (p = 0.003). All postoperative complications were not significantly different between groups (p > 0.05). Individual postoperative complications were combined and analyzed using a clustered approach to detect rates of complications more conservatively. Both the 7-system (5.1% versus 4.9%, p = 0.90) and 8-system (5.5% versus 4.9%, p = 0.72) clustered analyses were not significantly different before and after the initiation of the transfusion protocol. Conclusions: A restrictive transfusion protocol is effective in decreasing the number of units of blood transfused without affecting postoperative complication rates in gynecologic surgery patients.